Program Pemberdayaan Masyarakat Riau PT RAPP di Desa Banjar Benai Kecamatan Benai Kuantan Singingi - Suardl Tarumun (Universitas Riau, 2005)
This research reports the economic impact and the sustainahility of chili integrated farming in empoweringand reducing the poverty level in the village of Banjar Bcnai Kuantan Singingi. A-vsuming that the price levelof chili do not fluctuate widely this commodity will liltcly give a good additional source of income to farmers,even if all input and output are left determined by the marltct. If the produce to l e processed, it would likely Rive>farmers a stable income flows when the prices of chili are low.